2003
DOI: 10.1103/physrevb.67.045206
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational modes and electronic properties of nitrogen defects in silicon

Abstract: Nitrogen impurities form complexes with native defects such as vacancies and self-interstitials in silicon which are stable to high temperatures. These complexes can then suppress the formation of large vacancy and self-interstitial clusters. However, there is little known about their properties. We use first-principles densityfunctional theory to the determine the local vibrational modes, electrical levels and stability of a range of nitrogen-interstitial and vacancy complexes. Tentative assignments of the AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 83 publications
13
106
0
Order By: Relevance
“…The results of ab initio calculations may offer some insight into the structure of the defect found in this thesis. Calculations by Goss et al predict a level at E c -0.50eV due to the N s V defect [17]. It is possible that N s V is responsible for the deep-level observed in this work.…”
Section: Electrical Propertiesmentioning
confidence: 69%
See 2 more Smart Citations
“…The results of ab initio calculations may offer some insight into the structure of the defect found in this thesis. Calculations by Goss et al predict a level at E c -0.50eV due to the N s V defect [17]. It is possible that N s V is responsible for the deep-level observed in this work.…”
Section: Electrical Propertiesmentioning
confidence: 69%
“…Numerical simulations generally suggest that the nitrogen atoms in the dimer are strongly bound with an energy of 3.67 to 4.30eV [15][16][17] and that the dimer is practically immobile with an activation energy for diffusion of 2.38 to 2.69eV [18,19]. Experimental data obtained from a SIMS out-diffusion investigation give an activation energy for nitrogen transport as 2.8eV in the 800 to 1200ºC temperature range [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon lowering temperature, K decreases in proportion to exp(ÀE d /kT), where E d is the binding energy of a dimer, for which we adopt a value of 2.9 eV [11]. The first-principle estimates of E d give 3.6 eV [12] or 4.3 eV [13]. These energies are too large to agree with a relatively high value of K(T m ).…”
Section: Nitrogen States In Silicon Latticementioning
confidence: 99%
“…Jones et al (8) confirmed this conclusion using a combination of spectroscopic and ab-initio investigations. Except for the work of Gali et al (9), who calculated a binding energy of 1.73 eV, all theoretical investigations agree on a rather high binding energy between 3.67 and 4.3 eV (6,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 98%